TINJAUAN TERHADAP PENERAPAN AZAS LEGALITAS ADAT MINANGKABAU DALAM PUTUSAN MAKAMAH AGUNG NOMOR 839.K/PDT/2005 - Antony Firman (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract This research was conducted background review the Supreme Court decision that has been synchronized with the customary rules of Minangkabau to be able to give the settlement a dispute that occurred among people minang over ownership rights to the land that has been issued a certificate on behalf of the owner and issued a second time as a replacement for the previous certificate in the name of the expert next of kin, has issued the National Land Agency conducted the prosecution of issuance of certificates issued and declared unlawful. Against all the decision of the Court declared all files attached lawful and otherwise receive legal protection by the Supreme Court that states high court ruling does not fundamentally against the cancellation of the decision of the district court Painan. This research method is a normative juridical legal research process penganalisan appropriate decisions in accordance with laws and regulations applicable to the parties in obtaining the truth of proprietary rights held otherwise meet the elements of the agreement reached a consensus has been made by the parties to advance in legal actions on granting sebahagian Malay ethnic treasures given to his brother different tribes, different Ranji, different treasures, relics of the elders / fathers who are his own brother who was never questioned on their freelance grant had done.Behind the warring parties to fight the law on the release of the court's decision to appeal to the Supreme Court attached to the principle of lex superiori inferiori derogate lex (the law of higher legal mengeyampingkan lower), in the case of the determination decision that has had permanent legal force / Ingkracht. Defective or not a decision had to be reviewed from the principles of the decision contained in Article 50 of Law Number 48 Year 2009 concerning Judicial Authority and Article 178 HIR / 189Rbg contain a clear rationale and detailed enough discretion to excuse or onvoldoende gomotiveerd which can be taken into consideration certain Articles, legislation, common law, jurisprudence, or legal doctrine. In an effort peleksanaan command execution has the power executorial to decisions that are kondemnatoir an immediate emptying of a plot of land and / or buildings that exist dilahan dispute may be given legal protection include: 1. Preventive protection is through legislation in the implementation of the execution orders can be carried out immediately. 2. Protection of repressive law consists of (a) the protection of the law through litigation by Technical Directive No. 05 / JUKNIS / DV / 2007 on pelksanaan mechanisms of mediation and (b) protection of the law through litigation. Suggestions are given the results of this study is to assert the validity of a certificate is only the State Administrative Court / Administrative Court. Key words: determination, execution of the judgment, obtain legal protection Abstrak Penelitian ini dilakukan berlatar belakang tinjauan putusan Makamah Agung yang telah disingkronisasikan dengan aturan adat Minangkabau untuk dapat memberi penyelesaian perseteruan yang terjadi antara sesama orang minang atas kepemilikkan hak atas tanah yang telah diterbitkan sertifikat atas nama pemiliknya dan diterbitkan kedua kalinya sebagai pengganti sertifikat terdahulu atas nama ahli warisnya, telah dikeluarkan Badan Pertanahan Nasional dilakukan penuntutan atas terbitnya sertifikat yang dikeluarkan dan dinyatakan tidak sah menurut hukum. Terhadap semua putusan badan peradilan menyatakan semua berkas yang dilampirkan sah menurut hukum dan dinyatakan mendapat perlindungan hukum oleh Makamah Agung yang menyatakan putusan pengadilan tinggi tidak mendasar terhadap pembatalan putusan pengadilan negeri Painan. Metode penelitian ini yuridis normatif yang melakukan proses penganalisan keputusan menurut Peraturan Perundang-undangan, yang berlaku bagi para pihak dalam memperoleh kebenaran atas hak kepemilikan yang dimiliki dinyatakan memenuhi unsur kesepakatan yang mencapai kata mufakat. Para pihak dahulu di dalam melakukan perbuatan hukum atas pemberian sebahagian harta pusaka suku melayu yang diberikan pada saudaranya sendiri yang berbeda suku, berbeda ranji, berbeda harta pusaka, peninggalan para nenek mamak/ moyang yang merupakan saudaranya sendiri yang tidak pernah mempermasalahkan atas adanya pemberian hibah lepas yang telah dilakukannya. Pihak yang berseteru balik melakukan perlawanan hukum atas keluarnya putusan pengadilan tersebut sampai banding ke Makamah Agung melekat asas lex superiori derogate lex inferiori (hukum yang lebih tinggi mengeyampingkan hukum yang lebih rendah),Â Â dalam hal penetapan putusan yang telah mempunyai kekuatan hukum tetap/ Ingkracht. Dalam upaya perintah peleksanaan eksekusi yang mempunyai kekuatan eksekutorial terhadap putusan yang bersifat kondemnatoir segera dilakukannya pengosongan sebidang tanah dan/ atau bagunan yang ada dilahan sengketa dapat diberi perlindungan hukum diantaranya: 1. Perlindungan preventif yaitu melalui peraturan perundang-undangan dalam pelaksanaan perintah eksekusi tersebut dapat dilakukan segera. 2. Perlindungan hukum represif terdiri dari (a) perlindungan hukum melalui jalur litigasi berdasarkan Petunjuk Teknis Nomor 05/JUKNIS/D.V/2007 tentang mekanisme pelksanaan mediasi dan (b) perlindungan hukum melalui jalur litigasi. Saran yang diberikan hasil penelitian ini adalah yang dapat menyatakan sah atau tidaknya sebuah sertifikat hanyalah Peradilan Tata Usaha Negara/ PTUN. Kata kunci: penetapan, pelaksanaan putusan, mendapatkan perlindungan hukum